Perempuan dalam Novel â€œBidadari Bermata Beningâ€ Karya Habiburrahman El Shirazy - Anita Anita; Zainal Rafli; Siti Ansoriyah (Indonesian Language Education and Literature, 2020)
Women are considered weak and are considered inferior to men. This is widely used in novels as a form of literary work that can provide changes in thinking. The purpose of this research is to examine the value of women "Ayna" in the novel "Bidadari Bermata Bening" in terms of the theme. This qualitative research uses content analysis methods. The data sources are in the form of words, phrases and sentences in the novel. Based on the first theme, women experience family conflicts and are used for political purposes. Ayna is depicted as a figure of a woman who is acted on from a human rights perspective. The second theme is Ayna's struggle to achieve her dreams and love. Ayna is a smart woman who always carries out religious orders. The love that Ayna has is well guarded and finally, Ayna finds happiness.Perempuan dianggap kaum lemah dan dianggap lebih rendah dari laki-laki. Hal tersebut banyak diangkat dalam novel sebagai bentuk karya sastra yang mampu memberikan perubahan pemikiran. Tujuan penelitian ini adalah mengkaji nilai perempuan â€œAynaâ€ dalam novel â€œBidadari Bermata Beningâ€ ditinjau dari tema. Penelitian kualitatif ini menggunakan metode analisis isi. Sumber data berupa kata, frasa, dan kalimat dalam novel. Berdasarkan tema pertama, perempuan mengalami konflik keluarga, dimanfaatkan untuk kepentingan politik. Ayna digambarkan sebagai sosok perempuan yang tertindak dari segi hak kemanusiaan. Tema kedua adalah perjuangan Ayna dalam meraih cita-cita dan cintanya. Ayna menjadi sosok perempuan cerdas dan selalu menjalankan perintah agama. Cinta yang dimiliki Ayna dijaga dengan baik dan akhirnya Ayna mendapatkan kebahagiaan.